2018
DOI: 10.1002/jcp.27423
|View full text |Cite
|
Sign up to set email alerts
|

OCT4&SOX2‐specific cytotoxic T lymphocytes plus programmed cell death protein 1 inhibitor presented with synergistic effect on killing lung cancer stem‐like cells in vitro and treating drug‐resistant lung cancer mice in vivo

Abstract: This study aimed to investigate the synergistic effect of octamer-binding transcription factor 4 and sex determining region Y-box 2 (OCT4&SOX2)-specific cytotoxic T lymphocytes (CTLs) and programmed cell death protein 1 (PD-1) inhibitor on killing lung cancer stem-like cells (LCSCs) and their efficacy in treating drug-resistant lung cancer (DRLC) mice. OCT4&SOX2-specific CTLs and PD-1 inhibitor with differed doses were applied to treat PC9 cells and PC9 LCSCs. Cell counting kit-8 (CCK8) assay and flow cytometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…We found that patients with high SOX2 expression and high CD8+ TIL numbers demonstrated a favorable prognosis, and these constitute independent prognostic factors in LS-SCLC. SOX2-specific T-lymphocytes stimulated by CD154-activated B cells and with combined immune checkpoint inhibitors have a strong tumoricidal effect on lung cancer cell lines [32, 33]. SOX2 is also an endogenous target of T-cell immunity in non-SCLC.…”
Section: Discussionmentioning
confidence: 99%
“…We found that patients with high SOX2 expression and high CD8+ TIL numbers demonstrated a favorable prognosis, and these constitute independent prognostic factors in LS-SCLC. SOX2-specific T-lymphocytes stimulated by CD154-activated B cells and with combined immune checkpoint inhibitors have a strong tumoricidal effect on lung cancer cell lines [32, 33]. SOX2 is also an endogenous target of T-cell immunity in non-SCLC.…”
Section: Discussionmentioning
confidence: 99%
“…[ 49 ] The combined application of cytotoxic T lymphocytes and PD-1 inhibitor significantly decreased tumor volume and tumor weight in model mice, but promoted tumor necrosis and apoptosis compared with PD-1 inhibitor alone and blank control groups. [ 53 ] Thus, the presence of high NLR in lung cancer antagonized the therapeutic effects of PD-1/PD-L1 antibodies and resulted in the treatment failure. [ 54 ] The fact that high NLR could not predict the poor PFS for some patients receiving atezolizumab may be ascribed to their low PD-L1 expression (possible having other ligands [ 55 ] ) on neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…13 A number of studies reported that cytotoxic chemotherapy and targeted therapy kill the majority of cancer cells, except for CSCs. 32,33 Whether high expression level of Wnt5a promotes the resistance of first-generation EGFR-TKIs through CSCs need to be clarified. To improve the rationality of our hypothesis, we, in the present study, constructed a mouse xenograft model to analyze the relationship between the expression level of Wnt5a and CSCs.…”
Section: Discussionmentioning
confidence: 99%